PENGARUH JOB INSECURITY, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PADA KARYAWAN TETAP - Nurcahyati, Alfina; Irawanto, Dodi Wirawan (Jurnal Kewirausahaan dan Inovasi, 2023)
This research was conducted based on the fact that the number of layoffs in Indonesian bottled water companies are high despite the increasing demand. The objective of this research is to identify the effects of job insecurity, workplace environment, and work motivation on the job satisfaction of employees at PT Atlantic Biruraya Pasuruan, a company located in Pandaan of Sukorejo sub-district of Pasuruan Regency. The data of this quantitative explanatory study was harvested from questionnaires distributed to the company’s employees. Using saturated sampling, all 61 employees were selected as the respondents. The results of the multiple linear regression analysis indicate that job insecurity and work motivation have no significant effect on job satisfaction and that workplace environment positively and significantly influences the job satisfaction. Therefore, the company is suggested to improve its performance assessment system, pay more attention to the workload of their employees, and optimize employee empowerment to increase job satisfaction.